Associations with tight junction genes PARD3 and MAGI2 in Dutch patients point to a common barrier defect for coeliac disease and ulcerative colitisAn unusual case of ascites. Issue 4 (7th November 2007) - Wapenaar, M C; Monsuur, A J; van Bodegraven, A A; Weersma, R K; Bevova, M R; Linskens, R K; Howdle, P; Holmes, G; Mulder, C J; Dijkstra, G; van Heel, D A; Wijmenga, C
Abstract : Background: Coeliac disease (gluten-sensitive enteropathy; GSE) and inflammatory bowel disease (IBD) are common gastrointestinal disorders. Both display enhanced intestinal permeability, initiated by gluten exposure (GSE) or bacterial interactions (IBD). Previous studies showed the association of both diseases with variants in MYO9B, presumably involved in epithelial permeability. Aim: It was hypothesised that genetic variants in tight junction genes might affect epithelial barrier function, thus contributing to a shared pathogenesis of GSE and IBD. Methods: This hypothesis was tested with a comprehensive genetic association analysis of 41 genes from the tight junction pathway, represented by 197 tag single nucleotide polymorphism (SNP) markers. Results: Two genes, PARD3 (two SNPs) and MAGI2 (two SNPs), showed weak association with GSE in a Dutch cohort. Replication in a British GSE cohort yielded significance for one SNP in PARD3 and suggestive associations for two additional SNPs, one each in PARD3 and MAGI2 . Joint analysis of the British and Dutch data further substantiated the association for both PARD3 (rs10763976, p = 6.4×10 −5 ; OR 1.23, 95% CI 1.11 to 1.37) and MAGI2 (rs6962966, p = 7.6×10 −4 ; OR 1.19, 95% CI 1.08 to 1.32). Association was also observed in Dutch ulcerative colitis patients with MAGI2 (rs6962966, p = 0.0036; OR 1.26, 95% CI 1.08 to 1.47), and suggestive association with PARD3 (rs4379776, p = 0.068). Conclusions: These results suggest that coeliac disease and ulcerative colitis may share a common aetiology through tight junction-mediated barrier defects, although the observations need further replication.